2010
DOI: 10.24908/ss.v7i3/4.4154
|View full text |Cite
|
Sign up to set email alerts
|

Visual documentation as a normalizing practice: a new discourse of visibility in preschool

Abstract: The visual documentation of education for pedagogical purposes focuses on preschool children's activities and is used by educators to improve their understanding of children while strengthening their own professionalism. By analysing three educational TV programmes concerning visual documentation in preschools, this paper challenges the positivistic way visual documentation is portrayed. Moreover, it questions political documents and the TV programmes' unproblematic description of children as always ready to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
52
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 15 publications
1
52
0
7
Order By: Relevance
“…This documentation is supposed to focus on the practice rather than on individual children, but should also indicate 'how the child's knowledge changes and when they experience the preschool as interesting, fun and meaningful' (Swedish National Agency of Education, 2011, p.14). However, some research on preschool documentation has found that documentation focuses more on children as subjects of observation and surveillance than on teachers' practices and children's interest and learning (Sparrman & Lindgren, 2010;Vallberg Roth & Månsson, 2011).…”
Section: What Can Preschool Quality Become?mentioning
confidence: 99%
See 2 more Smart Citations
“…This documentation is supposed to focus on the practice rather than on individual children, but should also indicate 'how the child's knowledge changes and when they experience the preschool as interesting, fun and meaningful' (Swedish National Agency of Education, 2011, p.14). However, some research on preschool documentation has found that documentation focuses more on children as subjects of observation and surveillance than on teachers' practices and children's interest and learning (Sparrman & Lindgren, 2010;Vallberg Roth & Månsson, 2011).…”
Section: What Can Preschool Quality Become?mentioning
confidence: 99%
“…However, some research on preschool documentation has found that documentation focuses more on children as subjects of JOURNAL OF NORDIC EARLY CHILDHOOD EDUCATION RESEARCH VOL. 14(2), p. 1-17, 2017 ISSN 1890-9167 observation and surveillance than on teachers' practices and children's interest and learning (Sparrman & Lindgren, 2010;Vallberg Roth & Månsson, 2011).…”
Section: What Can Preschool Quality Become?mentioning
confidence: 99%
See 1 more Smart Citation
“…Preschool documentation as a pedagogical tool was common before the revised curriculum (Lenz Taguchi, 2000), and it has often been seen as unambiguously good, since it is sometimes argued that being seen is one part of becoming a subject (Sparrman & Lindgren, 2010). Traditionally, preschool observation and documentation has focused on what is general and normal in children of a certain age, according to theories of developmental psychology by Piaget and Erikson (WehnerGodée, 2000).…”
Section: Preschool Documentationmentioning
confidence: 99%
“…It can also be used to inform parents about what is going on in the preschool or for children to reflect on, discuss and remember what they have done or learned (Vallberg Roth, 2010). Documents are often displayed on walls for visitors to the preschool to see (Sparrman & Lindgren, 2010). Photographs and sometimes also short texts are occasionally shown publicly on preschools' websites or blogs.…”
Section: Preschool Documentationmentioning
confidence: 99%